Land-based Investments for rural development?: A grounded analysis of the local Impacts of biofuel feedstock plantations in Ghana - Schoneveld, George C.; German, L.; Nutakor, E. (2011)
The rapidly growing biofuel sector in Africa has, in recent years, been received with divided interest. As part of a contemporary wave of agricultural modernization efforts, it could make invaluable contributions to rural poverty. Conversely, it could also engender socioeconomically and environmentally detrimental land use changes as valuable land resources are converted to plantation agriculture. This research analyzes the impacts and impact pathways of biofuel feedstock development in Ghana. It finds that companies are accessing large contiguous areas of customary land through opaque negotiations with traditional authorities, often outside the purview of government and customary land users. Despite lack of participation, most customary land users were highly supportive of plantation development, with high expectations of ‘development’ and ‘modernization.’ With little opposition and resistance, large areas of agricultural and forested land are at threat of being converted to plantation monoculture. A case study analysis shows that this can significantly exacerbate rural poverty as communities lose access to vital livelihood resources. Vulnerable groups, such as women and migrants, are found to be most profoundly affected because of their relative inability in recovering lost livelihood resources. Findings suggest that greater circumspection by government is warranted on these types of large-scale land deals.